2007
DOI: 10.1007/s12035-007-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in Eating Disorders and Obesity

Abstract: Cannabinoid system is a crucial mechanism in regulating food intake and energy metabolism. It is involved in central and peripheral mechanisms regulating such behavior, interacting with many other signaling systems with a role in metabolic regulation. Cannabinoid agonists promote food intake, and soon a cannabinoid antagonist, rimonabant, will be marketed for the treatment of obesity. It not only causes weight loss, but also alleviates metabolic syndrome. We present a review of current knowledge on this subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…Long-term treatment with a CB1 receptor antagonist/ inverse agonist (SR141617A; rimonabant) led to effective sustained weight loss in rodent studies and human clinical trials, but a large number (26%) of the treated clinical population reported a profile of psychiatric side effects (including depression, anxiety, and agitation) [2,21]. Rodent models offer the advantage of assessing various aspects of eating behavior and diet without the constraints of the complex cognitive attributes that often accompany multifactorial human eating pathologies [33,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term treatment with a CB1 receptor antagonist/ inverse agonist (SR141617A; rimonabant) led to effective sustained weight loss in rodent studies and human clinical trials, but a large number (26%) of the treated clinical population reported a profile of psychiatric side effects (including depression, anxiety, and agitation) [2,21]. Rodent models offer the advantage of assessing various aspects of eating behavior and diet without the constraints of the complex cognitive attributes that often accompany multifactorial human eating pathologies [33,73].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, diet-induced obesity produced a down-regulation of the CB1 receptor in several brain regions [13,14,16,17], whereas prolonged treatment with a CB1 antagonist or disruptions in the CB1 receptor gene reduce food intake and adiposity, and prevents the development of diet-induced obesity [18-20]. As a result, normalization of the endogenous cannabinoid system by reducing CB1 signaling has generated considerable therapeutic interest for the treatment of obesity [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…A third major circuit for appetite and body weight regulation that is a candidate for obesogenic disruption involves the endocannabinoid system (ECS) pathway (reviewed in [136]). Endogenous or dietary agonists of the cannabinoid receptor type 1 (CB1), including the lipid derivatives anandamide (AEA) and 2-arachidonyl glycerol (2-AG), have central orexigenic effects in the hypothalamus, even in satiated animals [137], and impact metabolic functions in peripheral tissues including adipose.…”
Section: Obesogens and Central Integration Of Energy Balancementioning
confidence: 99%
“…Although several classes of drugs including cannabinoids, (Corey, 2005;Rockwell et al, 1984;Volicer et al, 1997) have been tried as therapy for anorexia nervosa, to date no medication, alone or in combination with other therapies, has been demonstrated to be effective in the treatment of the primary disorder (Israel, 2005). However, anorexia, marked by decreased food intake has been reported as one of the withdrawal effects in over 50% of individuals who smoke marijuana repeatedly through out the day, 6-7 days per week in laboratory and clinical studies (Haney et al, 2008;Horcajadas, 2007). In one study, Haney et al, (2008) reported that a combination of THC and lofexidine, a centrally acting a 2 -agonist, produced the most robust improvements in marijuana withdrawal effects relative to either medication alone (Haney et al, 2008;Horcajadas, 2007).…”
Section: Introductionmentioning
confidence: 99%